The Effect of Skill Exercises Using Cooperative Learning On Learning High Dribbling and Rebound Pass In Basketball For Second Grade Secondary School Students - Sadi, Maitham; Ali, Ishraq (Journal of Physical Education, 2019)
The research aim at identifying the effect of skill exercises using cooperative learning in dribbling and rebound passing skills learning in second grade secondary school students. The researchers used the experimental method. The training program was applied on (30) students divided into two groups; cooperative learning group and traditional learning controlling group. The data was collected and treated using proper statistical operations to conclude that the proposed exercises have an effective role in learning passing and dribbling for second grade secondary school students. Finally the researchers recommended benefiting from cooperative learning in learning some basic skills in basketball as well as enhancing cooperative learning style by holding training courses for improving the skills required for applying this style.